A critical legal analysis of General Comment No. 4 on Article 24 (Education) of the Convention on the Rights of Persons with disabilities - N. Sairankyzy (Bulletin of the Karaganda University “Law Series”, 2025)
The article examines the international and national legal frameworks governing the right to inclusive educa tion, with a particular focus on the interpretation and application of Article 24 of the United Nations Conven tion on the Rights of Persons with Disabilities. The objective of the study is to examine the nature and scope of state’s legal obligations. The study adopts a comparative legal analysis and interpretation of international legal documentation, with a particular emphasis on General Comment No. 4 of the Committee on the rights of persons with disabilities. The study identifies legal and practical contradictions, particularly with regard to the transformation of special educational institutions and the role of parents in choosing their child’s educational form. The findings of the study provide substantiation for the perspective that inclusive education ought to be recognised not solely as a pedagogical or social paradigm but also as an individual right. The article con cludes with a recommendation that inclusive and special education should be legally coordinated, and that learning environment should be created in the best interests of the child. Inclusion should be conceptualised as a complementary component of an integrated education system, rather than a complete replacement for special education.